2021
DOI: 10.1177/1464420720985899
|View full text |Cite
|
Sign up to set email alerts
|

The effect of variable properties and rotation in a visco-thermoelastic orthotropic annular cylinder under the Moore–Gibson–Thompson heat conduction model

Abstract: The present contribution aims to address a problem of thermoviscoelasticity for the analysis of the transition temperature and thermal stresses in an infinitely circular annular cylinder. The inner surface is traction-free and subjected to thermal shock heating, while the outer surface is thermally insulated and free of traction. In this work, in contrast to the various problems in which the thermal conductivity coefficient is considered to be fixed, this parameter is assumed to be variable depending on the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 56 publications
5
27
0
Order By: Relevance
“…This important conclusion demonstrates the importance of the proposed model, in which the problem of the physical inconsistency found in the CPTE and PGN-III models has been solved. This is fully consistent with the claims of Quintanilla [21] and Abouelregal et al [23][24][25][26].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This important conclusion demonstrates the importance of the proposed model, in which the problem of the physical inconsistency found in the CPTE and PGN-III models has been solved. This is fully consistent with the claims of Quintanilla [21] and Abouelregal et al [23][24][25][26].…”
supporting
confidence: 91%
“…The energy Equation ( 7), when combined with the enhanced Fourier law presented in (6), has the same flaw as Fourier's normal model, anticipating that the heat waves will spread quickly. After including the relaxation parameter into the GN-III model, Quintanilla [21,22] and Abouelregal et al [23][24][25] developed the suggested updated heat equation. Fourier's law was proposed to be [21,22] 1…”
Section: Formulating Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of several mechanical aspects of the flux, this theory started with a third-order differential equation. The MGT thermoelastic model has led to a significant increase in the range of researchers devoted to this theory [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This theory began with a third-order differential equation created in the context of fluid mechanics. Since the introduction of the MGT theory [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], many researchers have devoted their efforts to studying this new model.…”
Section: Introductionmentioning
confidence: 99%